KEMAMPUAN PENALARAN MATEMATIS DITINJAU DARI KECERDASAN SPASIAL SISWA SMP NEGERI 3 BANYUMAS - Muhammad Afif Tanzani (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2017)
This research aimed to describe students' mathematical reasoning ability viewed from spatialintelligence in SMP Negeri 3 Banyumas. This was conducted in Grade VIII A SMP Negeri 3Banyumas. The method of this research was qualitative descriptive. The sampling techniquewas purposive sampling. The subjects were divided into three groups; group with high spatialintelligence, group with medium spatial intelligence, and group with low spatial intelligence.The techniques of collecting data were test and interview. The result of this research showsthat: (1) Students with high spatial intelligence were able to master six indicators ofmathematical reasoning ability such as proposing presumption, finding the pattern to makegeneralization, drawing conclusion from the statements, proving the truth of a solution, doingmathematic manipulation, and checking the validity of an argument; (2) Students withmedium spatial intelligence were able to master four indicators of mathematical reasoningability such as proposing presumption, finding the pattern to make generalization, doingmathematic manipulation, and checking the validity of an argument; and (3) Students withlow spatial intelligence were able to master three indicators of mathematical reasoning abilitysuch as proposing presumption, drawing conclusion from the statements, and doingmathematic manipulation.KEY WORDS: Mathematical Reasoning Ability, Spatial Intelligence